A web-based system for early detection of symptom of depression. (1st January 2014) - Pandya, Bhairavi D.; Mital, Dinesh P.; Srinivasan, Shankar; Haque, Syed
According to the World Health Organization, depression affects about 121 million people worldwide. The Centers for Disease Control report in the USA an estimated 10% of the population will be affected by depression in a given year. We developed the patient data management system (PDMS) to determine if a web-based system can be effectively utilised for the early detection of depressive symptoms. There were 394 participants in the study, 65.5% (N = 258) were female and 34.5% (N = 136) were male. In summary, 89.9% of the population (N = 354) was not depicting any depression symptoms according to CES-D score. The frequency of positive depression screening (indicated by a CED-S score of > 16) was observed in 10.16% (N = 40) of the total population. There was a significant effect of gender on higher CES-D score at p < .05 level for the subjects in the study [F (1, 392) = 11.34, p = .001].